The impact of management traps on surgical strategies in parathyroid benign and malignant tumors-related PHPT: a retrospective cohort study - Zhu, Guang-wen; Lv, Xue; Jiao, Zhan (Frontiers in Oncology, 2025)
BackgroundReducing the incidence rate of persistent/recurrent HPT after surgery is the key to the treatment of PHPT. The pitfalls of preoperative, intraoperative, and postoperative management in PHPT patients and their potential impact on surgical strategies need to be comprehensively investigated.MethodsThe demographic, biochemical, radiological results and other clinical data of the enrolled 112 patients with primary hyperparathyroidism undergoing surgical treatment were obtained from our database in this retrospective cohort study. One-way analysis of variance was used for normally distributed variables, and Kruskal-Wallis H test was used for non-normally distributed variables. Pearson’s chi-square test or Fisher’s exact test was used for categorical variables, as appropriate.ResultsThe patients were divided into parathyroid adenoma group and atypical parathyroid tumor + parathyroid carcinoma group. The serum calcium levels, serum PTH levels in the APT+PC group were higher than those with benign lesions, but there was some overlap; and the clinical data showed no specificity in the differentiation of benign and malignant parathyroid tumors. A more significant finding in this cohort was that the tumor size was significantly larger in persistent/recurrent HPT group than in non-persistent/recurrent group (30.0 ± 12.6 mm vs.19.1± 8.3 mm, p < 0.01).ConclusionIn PHPT, there are pitfalls in preoperative, intraoperative, and postoperative management of parathyroid tumors, which affect the choice of surgical strategies. It is prudent to utilize the tumor-free margin En bloc resection in a variety of parathyroid neoplasms, in order to seek the chance of cure and avoid reoperation as much as possible.